Chapter Preparing Proteoforms of Therapeutic Proteins for Top-Down Mass Spectrometry - Heikaus, Laura (InTechOpen, 2019)
A characteristic of many proteoforms, derived from a single gene, is their similarity regarding the composition of atoms, making their analysis very challenging. Many overexpressed recombinant proteins are strongly associated with this problem, especially recombinant therapeutic glycoproteins from large-scale productions. In contrast to small molecule drugs, which consist of a single defined molecule, therapeutic protein preparations are heterogenous mixtures of dozens or even hundreds of very similar species. With mass spectrometry, currently high-quality spectra of intact proteoforms can be obtained only, if the complexity of the mixture of individual proteoform-ions, entering the gas phase at the same time is low. Thus, prior to mass spectrometric analysis, an effective separation is required for getting fractions with a low number of individual proteoforms. This is especially true not only for recombinant therapeutic proteins, because of their huge heterogeneity, but also relevant for top-down proteomics. Purification of proteoforms is the bottleneck in analyzing intact proteoforms with mass spectrometry. This review is focusing on the current state of the art, especially of liquid chromatography for preparing proteoforms for mass spectrometric top-down analysis. The topic of therapeutic proteins has been chosen, because this group of proteins is most challenging regarding their proteoform analysis.